Proses Pembelajaran Matematika pada masa Covid-19 di MAN 2 Langkat - Faisal, Faisal; Imron, Dwi Santika (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
The purpose of this research was to determine the process and evaluation of learning mathematics during the Covid-19 period at MAN 2 Langkat. This research is a qualitative research with research subjects, namely one teacher and one student. The data collection techniques used were interviews and documentation. Data analysis is categorized into three stages, namely reduction, data presentation, and drawing conclusions. The results showed that learning during the covid-19 pandemic at MAN 2 Langkat began with providing information by the teacher through the Watshapp group regarding learning time and materials to be discussed. After that the teacher directed the students to read and understand the materials. Learning is continued by using various applications such as zoom, Schoology, Edmodo, and Google Classroom. The assessment of student learning outcomes during the Covid-19 period was carried out covering only two aspects, namely cognitive and affective. For the cognitive assessment forms using daily tests, biweekly tests, midterm and end-of-semester tests. Meanwhile, my form of affective assessment refers to student attendance, diligence, discipline and learning participation.